Inovasi Layanan Pertanahan Berbasis Teknologi: Implementasi Aplikasi Sentuh Tanahku dalam Pendaftaran Tanah - Aurelia, Sylvania Okta; Listyani, Alvi Septia; Saputri, Syaefwanda Agita; Herawati, Sukma; Niravita, Aprila; Fikri, Muhammad Adymas Hikal (JURNAL ILMIAH NUSANTARA, 2025)
This study examines the innovation of land administration services through the Sentuh Tanahku application as part of the implementation of electronic land registration in Indonesia. Using a qualitative descriptive method and document analysis of regulations, official reports, and academic studies, this research evaluates the application’s integration with the Land Administration Computerization System (KKP), its user workflow, and the effectiveness of its implementation across different regions. The findings show that the application significantly enhances transparency, efficiency, and accountability in land services, particularly in urban areas with adequate digital infrastructure. However, challenges persist in regions with limited internet access and insufficient human resource capacity. Despite these obstacles, the acceleration of electronic certificate issuance and increasing user satisfaction indicate that Sentuh Tanahku plays a crucial role in driving the digital transformation of land administration. The study highlights the need for equitable infrastructure development, improved human resource readiness, and further optimization of application features to support nationwide implementation of electronic land services.